Remapping Soil Fertility: A Chemical Approach to Optimizing AgriculturalLand in Urban Area of Bandulan Village, Malang City - Nareswari, Ayu; Rafi Ahdan Rizar, Mohamad (Badan Perencanaan Pembangunan Kota Malang, 2024)
This study explores soil fertility optimization strategies in Bandulan Village, Sukun District, Malang City, through a chemical analysis approach. The main focus of this study is to identify soil chemical parameters such as pH, nitrogen (N), phosphorus (P), and potassium (K), which affect agricultural productivity in urban areas with limited land. The methods used include laboratory testing and field observations to provide a comprehensive assessment of soil conditions. The results showed that soil fertility in the study area was at a moderate level, with pH varying from moderately acidic to slightly acidic, and N, P, and K contents ranging from low to moderate. These conditions can inhibit plant growth if not managed properly, especially in soils with a more acidic pH. This study offers recommendations for farmers and policy makers to improve efficient soil management through the use of organic fertilizers, technology-based soil fertility monitoring, and the adoption of environmentally friendly agricultural practices. Thus, it is expected to support the sustainability of agriculture amidst the pressures of urbanization and environmental change.